The Use of Mind Maps and Educational Snakes and Ladders to Overcome Learning Difficulties in Acids and Bases - Naya Mahdiyya Sari; Mahrus Mahrus; M. Rata; Fadlurrahman Hadi Nugroho (Yayasan Siti Widhatul Faeha Salahudin Syawal, 2026)
Low level of students’ conceptual understanding and engagement in learning chemistry, particularly on acid-base topics. The purpose of this study is to analyze the effectiveness of ethnoscience-based mind map wall displays and an educational Snakes and Ladders game in improving students’ conceptual understanding and motivation to learn. The study employed a qualitative classroom action research design conducted in two cycles, involving 67 eleventh-grade students at SMAN 4 Mataram, with data collected through observations, student worksheets, and learning evaluations. The results indicate a significant improvement in students’ conceptual understanding, active participation, and learning outcomes, as evidenced by more than 80 percent of students achieving scores above the minimum competency criteria and an increase in the average score from 62 to 81, along with positive student responses toward a more interactive and contextual learning process. In conclusion, the integration of visual, ethnoscience-based, and gamification-oriented learning media is effective in enhancing the quality of chemistry learning, particularly on acid-base material. This study suggests that innovative, contextual, and game-based learning strategies can serve as effective alternatives for improving the quality of science education.